Projecting food-energy-water sustainability through ecosystem service modeling under climate and land use change in a subtropical agricultural watershed - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chiao-Ming Lin; Gerard H. Ros (Agricultural Water Management)
Managing food–energy–water (FEW) resources in the face of climate change presents significant challenges, particularly owing to a limited understanding of the spatiotemporal dynamics of ecosystem service (ES)-driven FEW sustainability. This study presents a novel approach to evaluate FEW sustainability under climate and land use changes by utilizing ES values instead of the supply-demand of FEW resources for the Zhuoshui Watershed in Taiwan. We integrate the Conversion of Land Use and its Effects on the Small Regional Extensions model and three general circulation models under the RCP 8.5 scenario to simulate land use change under climate change. Associated ES changes are estimated using the InVEST model, identifying ES hotspots with Local Indicators of Spatial Association and quantifying FEW sustainability through geographically weighted regression methods (R2 = 0.65). Land use changes significantly influenced ES provision, with conservation areas enhancing ecological resilience and water sustainability. ES hotspots were associated with higher water security but faced trade-offs in food and energy subsystems. Changes in land use and associated ES strongly influenced FEW sustainability, particularly in conservation areas, by promoting ecological resilience and sustainable resource management. Key measures include ecosystem-based spatial planning and strategies for FEW sustainability under climate change. These measures help maintain enhanced ES provision, improve sustainability projections, and support evidence-based policies for long-term environmental sustainability. Hotspot regions exhibit higher water sustainability but will be increasingly pressured regarding food and energy resources.